Contributing to business ethics though thick conceptualization - Greenwood, Michelle ca. 20./21. Jh. (Journal of business ethics, 2025)
In this editorial essay we argue that contribution to business ethics theory and practice can be achieved through thick ethical conceptualization, that is, by working with concepts in a manner that is both deeply descriptive and normative. Rather than foreclose on what is ethical or unethical, good or bad, permissible or impermissible, we encourage all authors submitting to the Journal of Business Ethics to carefully and clearly explicate their ethical analysis of their study’s focal phenomena. For empirical papers this means they should "explain the ethics" within their descriptions of empirical phenomena, while for normative ethical papers it means that authors should embed their analysis in a thick understanding of the contexts in which these analyses are applied. Understanding concepts as both descriptive and normative provides stronger conceptualization and capacity to theorize. It also provides greater nuance to recognize and interpret novel and complex findings. Below, we offer some reflections about the varieties of ethical "thinning" and ideas about how authors can work with thick concepts to make an ethical contribution.